Application of Demonstration Methods to Improve Learning Achievement in Cultural Arts Subject and Skills of Filter Art Graphic Materials in Class IX E Students of SMP Negeri 3 Surabaya - Mustamir, Ahmad (Indonesian Journal of Contemporary Education, 2019)
This study aims to determine the increase in learning achievement of students of class IX E of SMP Negeri 3 Surabaya through the application of Demonstration methods in SBK lessons on filter print graphic art material. This type of research is classroom action research (CAR) carried out in 2 cycles of action. The research subjects were 38 people consisting of 15 male students and 23 female students. The research data was collected using observation methods and interview methods with assessment rubric instruments. Data from the research results were analyzed using descriptive statistical analysis methods and quantitative descriptive analysis methods. The results of data analysis showed that there was an increase in the learning outcomes of students of class IX E of SMP Negeri 3 Surabaya from the application of the demonstration method with the printing technique reaching 12.45%. In the first cycle of 79.88% who were in the low criteria experienced an increase in the second cycle to 92.33% classified as high criteria. Thus it can be concluded that the application of the demonstration method with printing techniques can improve the learning achievement of class IX E students of SMP Negeri 3 Surabaya on filter print graphic art material.